BEYOND THE IMPLEMENTATION OF PROJECT-BASED ASSESSMENT IN ELT: BENEFITS, CHALLENGES, AND TEACHERS' STRATEGIES - Navisatul Izzah; Laksmi Diana (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
There have been many assessment methods used in ELT classrooms, including project-based assessment. However, little is known about why this assessment method is suggested, what should be anticipated in the classroom, and how teachers overcome issues in the classroom.  Regarding those research gaps, this paper aims to investigate the benefits, emerging challenges, and strategies from the teachers’ point of view. This study uses a qualitative case study as the research method to investigate the topic raised in depth. The findings show four benefits offered by the project-based assessment such as the improvement of students’ collaboration and teamwork skills, students’ creativity, critical thinking skills and bonding between students. The challenges were students’ time management and free-riders. The teacher participants in this study overcame these challenges by grouping students, structuring the tasks and motivating students, collaborating with other subjects, and conducting self and peer-assessment.